Discovery of novel triazole-containing pyrazole ester derivatives as potential antibacterial agents - Chu, Ming-Jie (2019)
To develop new antibacterial agents, a series of novel triazole-containing pyrazole ester derivatives were designed and synthesized and their biological activities were evaluated as potential topoisomerase II inhibitors. Compound 4d exhibited the most potent antibacterial activity with Minimum inhibitory concentration (MIC) alues of 4 µg/mL, 2 µg/mL, 4 µg/mL, and 0.5 µg/mL against Staphylococcus aureus, Listeria monocytogenes, Escherichia coli, and Salmonella gallinarum, respectively. The in vivo enzyme inhibition assay 4d displayed the most potent topoisomerase II (IC50 = 13.5 µg/mL) and topoisomerase IV (IC50 = 24.2 µg/mL) inhibitory activity. Molecular docking was performed to position compound 4d into the topoisomerase II active site to determine the probable binding conformation. In summary, compound 4d may serve as potential topoisomerase II inhibitor.